Flood warning system in Malaysia - Illuni Syairah Binti Zulkefli (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
Flood is such a natural disaster that cannot be predicted which represents a significant hazard to human safety and a threat to property. The reason comes with no proper warning to them. In this project, the system is direct to the risky areawhich focusing on measuring the water level of the river. A sensor is going to place and seal-in at the wood placed in the river, so then whenever the water level of the river rise up, the sensor will detect and the information by the sensor is send directly to PIC. The PIC that is generated by 12V battery will interpret the data of water level all the time being (real-time data) as it is operated 24 hours. The output medium of this system in order to displays the reading is by using LCD 16X2, LED and the buzzer for sound. This stand-alone concept offlood warning system is created to give the information and early warning at the risky area and control room unit of flood disaster which is focusing on displaying the water level of the nearly river.The LCD, LED and buzzer is used to give the warning directly if the situations comes worst with as minimum as can the risk of the flood. The PIC type that will be used for this project is PIC16F877A.